Comparison of Breast Reconstruction Outcomes Using Oxychlorosene versus Triple Antibiotic Solution for Pocket Irrigation. Issue 8 (18th August 2022) - Bamba, Ravinder; Tran, Phu C.; Mailey, Brian A.; Lin, Jenny; DeBrock, William; Dawson, Steven; Sinha, Mithun; Hartman, Brett C.; Hadad, Ivan; Lester, Mary E.; Hassanein, Aladdin H.
Abstract : Background: Breast pocket irrigation with antiseptic solutions is performed to reduce contamination with breast implants. The optimal antiseptic irrigation solution and the efficacy of individual practices are unclear. Oxychlorosene sodium is frequently used at our institution. Oxychlorosene is bactericidal with a mechanism of action of oxidation and hypochlorination. The purpose of our study was to compare the outcomes of oxychlorosene sodium irrigation with triple antibiotic solution (TAS) in implant-based breast reconstruction. Methods: All patients who underwent implant-based reconstruction after mastectomy were reviewed. The primary predictive variable was type of solution used for pocket irrigation (TAS or oxychlorosene). Outcome variables included surgical site infection, device removal, and wound complications. Results: Between 2013 and 2018, 331 implant-based breast reconstructions were performed. Of these, 62% (n = 206) received oxychlorosene for surgical pocket irrigation (group I), and 38% (n = 125) received TAS (group II). Group I had an 11.7% (n = 24) 90-day surgical site infection rate, with 4.9% (n = 10) requiring oral antibiotics, 2.4% (n = 5) requiring intravenous antibiotics without device removal, and 4.4% (n = 9) requiring prosthetic removal. Group II had an 11.2% (n = 14) 90-day infection rate, with 5.6% (n = 7) requiring oral antibiotics, 2.4% (n = 3) requiring intravenous antibiotics without device removal, and 3.2% (n = 4) requiring removal ( P = 0.90). When comparing the cost of oxychlorosene irrigation with TAS irrigation, oxychlorosene was less expensive. Conclusions: Oxychlorosene and TAS have similar surgical site infection rates in prosthetic breast reconstruction. Ease of preparation and cost make oxychlorosene a more favorable option for antibiotic irrigation in reconstructive breast surgery with prosthetic devices.